Evaluation of the Toxicity and Neurological Effects of Fulranumab in Adult Cynomolgus Monkeys. (May 2019) - Rocca, Meredith; Han, Chao; Butt, Mark; Coogan, Timothy P.
Fulranumab, an anti-human nerve growth factor antibody, was evaluated in a series of nonclinical toxicology studies. No treatment effects were observed in adolescent cynomolgus monkeys in standard design, repeat-dose toxicology studies of up to 6 months. Adverse effects on the developing nervous system were observed in offspring of pregnant cynomolgus monkeys treated with fulranumab. Subsequent studies including detailed morphologic investigations of the nervous system did reveal fulranumab-related changes in adult cynomolgus monkeys; this article is focused on those findings. A single dose of ≥1 mg/kg fulranumab administered subcutaneously (SC) caused a decrease in neuron and sympathetic ganglion size (superior cervical ganglion), observed morphologically and stereologically, with a resulting appearance of increased glial cell density. Similar results were observed in repeat-dose (15 to 52 weeks) toxicity studies at ≤50 mg/kg/wk fulranumab SC. These effects recovered after a 3-month treatment-free period. Fulranumab did not cause any neuronal death, necrosis, apoptosis, or any apparent decrease in function of sympathetic neurons/ganglia at any time point examined. A no observed effect level (NOEL) was established at 0.25 mg/kg fulranumab SC every 4 weeks for 28 weeks.